RISK ASSESSMENT KECELAKAAN KERJA PADA PEKERJAAN AIRCRAFT PAINT REMOVAL DI PT. X - Hesti Fiskalisa Purbayanti; Sho'im Hidayat (The Indonesian Journal of Occupational Safety and Health, 2018)
The entire activity involving human factors, machinery, chemicals, and through some work processes had the potential hazard that increased the risk of accidents and health problems. Aircraft paint removal job was a high risk of an accident. The purpose of this research was to identify hazards, assess pure risks, identify risk control, and assess risks after risk control were conducted on aircraft paint removal job in  PT. X. Type of this research was descriptive research. Primary data retrieval techniques in the study was observational and interview. The subject of research were 1 PDCA HSE and 4 aircraft paint removal workers. Variable in this study is the hazards, likelihood, severity, risk levels, and risk control. The results of hazard identification obtained 14 risk in Aircraft Paint Removal such as 1 low risk, 2 middle risks and 13 high risks. Risk control by the company showed that there are 13 high risk decrease to 7, 2 middle risks increased to 6 risk, and 1 low risk increased to 3 risks. In conclusion, PTX. has 14 risks, 13 of them included in the high risk category. There was a decrease in risk due to the control carriedd out by the company into 13 risks and 7 of them included in high risk.Keywords: aircraft paint removal, hazard identification, risk assessment, risk control